Irony in Jonathan Glazer’s The Zone of Interest (2023): A Cinematographic Analysis of Long Shot. - Haykal, Muhammad; Ruminda, Ruminda; Sudarisman, Yoga (Universitas Pahlawan Tuanku Tambusai, 2025)
This research examines how irony is conveyed through long shot cinematography in Jonathan Glazer’s The Zone of Interest (2023). Using Joseph M. Boggs and Dennis W. Petrie’s six types of irony such as dramatic, situational, character, setting, tone, and cosmic as the main framework, the research analyzes how these forms manifest visually through cinematic language. Set in the domestic sphere of Auschwitz commandant Rudolf Höss, the film employs visual distance and static framing to juxtapose everyday normalcy with atrocities occurring beyond the frame. Adopting a qualitative descriptive method, and drawing on theories from Mario Klarer and Gustavo Mercado, the analysis reveals that long shots function not only to emphasize physical and emotional detachment but also to heighten ironic contrast between visual calm and unseen violence. This creates a compelling visual irony that confronts viewers with the moral indifference and normalized evil within the setting. The research contributes to broader discussions on how irony in films can represent historical trauma through indirect yet deeply affective cinematic strategies.